2014
DOI: 10.1039/c3cp54800g
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear manganese complexes for water oxidation: evaluation of electronic effects and catalytic activity

Abstract: During recent years significant progress has been made towards the realization of a sustainable and carbon-neutral energy economy. One promising approach is photochemical splitting of H2O into O2 and solar fuels, such as H2. However, the bottleneck in such artificial photosynthetic schemes is the H2O oxidation half reaction where more efficient catalysts are required that lower the kinetic barrier for this process. In particular catalysts based on earth-abundant metals are highly attractive compared to catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 86 publications
3
52
0
Order By: Relevance
“…380 Further Following the work on complex 295, the group of Åkermark prepared a series of analogous dimeric Mn 2 II,III complexes bearing various substituents in the para position of the phenol motif. 382 All complexes had a sufficiently low redox potential to allow H 2 O oxidation to be driven by [Ru(bpy) 3 ] 3+ . Among the investigated WOCs, complex 297 ( Figure 78) containing a long alkyl chain with a terminal carboxylate group was found to be the most efficient catalyst.…”
Section: Manganese-based Catalysts Capable Of Generating Oxygenmentioning
confidence: 99%
“…380 Further Following the work on complex 295, the group of Åkermark prepared a series of analogous dimeric Mn 2 II,III complexes bearing various substituents in the para position of the phenol motif. 382 All complexes had a sufficiently low redox potential to allow H 2 O oxidation to be driven by [Ru(bpy) 3 ] 3+ . Among the investigated WOCs, complex 297 ( Figure 78) containing a long alkyl chain with a terminal carboxylate group was found to be the most efficient catalyst.…”
Section: Manganese-based Catalysts Capable Of Generating Oxygenmentioning
confidence: 99%
“…These findings confirmed that 93 was intact under water oxidation conditions. Inspired from the research work on 93, Åkermark synthesized some similar dimeric Mn 2 II, III complexes containing different substituentsin the para position of the phenol motif 133. All synthesized complexes were catalytically active for water oxidation reaction and had a sufficiently low redox potential to permit water oxidation to be driven by [Ru(bpy) 3 ] 3+ at neutral reaction conditions.…”
mentioning
confidence: 99%
“…[59] The imidazole ligand can promote proton transfer because the oxidation states of the Mn species vary,t hus indicating the importance of ligands for the water oxidation reaction. [60] The experimental results showedt hat the catalyst with ac arboxylic group at the end had ah igher activity, which might originate from the hydrogen bond between the carboxylic group and the high oxidation state of Mn. [56].C opyright:2 015 American Chemical Society.…”
Section: Binuclearmanganese-based Catalystsmentioning
confidence: 97%
“…[ www.chemsuschem.org the ligands. [60] The experimental results showedt hat the catalyst with ac arboxylic group at the end had ah igher activity, which might originate from the hydrogen bond between the carboxylic group and the high oxidation state of Mn.…”
Section: Binuclearmanganese-based Catalystsmentioning
confidence: 97%